2020
DOI: 10.3390/ijerph17103665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plyometric versus Ankle Stability Exercises on Lower Limb Biomechanics in Taekwondo Demonstration Athletes with Functional Ankle Instability

Abstract: Background: This study aimed to compare the effects of plyometric and ankle stability exercises on the dynamic balance and lower limb kinematic and kinetic parameters of Taekwondo demonstration athletes with functional ankle instability. Methods: Fourteen subjects participated in this study and were randomly divided into two groups: a plyometric exercise group (n = 7) and an ankle stability exercise group (n = 7). Exercises were performed twice a week for 8 weeks. A Y-balance test was used to measure dynamic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Forty-two studies were included for qualitative assessment: (Witzke and Snow, 2000 ; Myer et al, 2006 ; McLeod et al, 2009 ; Asadi and Arazi, 2012 ; Asadi, 2013 ; Chaouachi et al, 2014a , b ; Faigenbaum et al, 2014 ; Huang et al, 2014 ; Piirainen et al, 2014 ; Asadi et al, 2015 ; Ramírez-Campillo et al, 2015a , b ; Trecroci et al, 2015 ; Benis et al, 2016 ; Karadenizli, 2016 ; Kim and Park, 2016 ; Hopper et al, 2017 ; Nobre et al, 2017 ; Arabatzi, 2018 ; Makhlouf et al, 2018 ; Ritzmann et al, 2018 ; Alikhani et al, 2019 ; Cherni et al, 2019 ; Hammami et al, 2019a , b , c , 2020a , b , c ; Jlid et al, 2019 , 2020 ; Lovecchio et al, 2019 ; Meszler and Váczi, 2019 ; Tay et al, 2019 ; Akin and Kesilmiş, 2020 ; Bouteraa et al, 2020 ; Cigerci and Genc, 2020 ; Drouzas et al, 2020 ; Lee et al, 2020 ; Surakhamhaeng et al, 2020 ; Porrati-Paladino and Cuesta-Barriuso, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-two studies were included for qualitative assessment: (Witzke and Snow, 2000 ; Myer et al, 2006 ; McLeod et al, 2009 ; Asadi and Arazi, 2012 ; Asadi, 2013 ; Chaouachi et al, 2014a , b ; Faigenbaum et al, 2014 ; Huang et al, 2014 ; Piirainen et al, 2014 ; Asadi et al, 2015 ; Ramírez-Campillo et al, 2015a , b ; Trecroci et al, 2015 ; Benis et al, 2016 ; Karadenizli, 2016 ; Kim and Park, 2016 ; Hopper et al, 2017 ; Nobre et al, 2017 ; Arabatzi, 2018 ; Makhlouf et al, 2018 ; Ritzmann et al, 2018 ; Alikhani et al, 2019 ; Cherni et al, 2019 ; Hammami et al, 2019a , b , c , 2020a , b , c ; Jlid et al, 2019 , 2020 ; Lovecchio et al, 2019 ; Meszler and Váczi, 2019 ; Tay et al, 2019 ; Akin and Kesilmiş, 2020 ; Bouteraa et al, 2020 ; Cigerci and Genc, 2020 ; Drouzas et al, 2020 ; Lee et al, 2020 ; Surakhamhaeng et al, 2020 ; Porrati-Paladino and Cuesta-Barriuso, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, our meta-analysis revealed that when PJT was compared with balance training, both training types induced similar balance adaptations ( p = 0.510 between training methods). Plyometric jump training has the potential to improve muscle strength, power, and balance through primarily neural adaptations (Lee et al, 2020 ). Compared to other training types, PJT exercises involve the braking (eccentric) and propulsion (concentric) phases performed in the SSC which, when applied over longer periods, improve muscle strength, power, and speed (Komi and Gollhofer, 1997 ; Taube et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance ability and the functional performance [ 15 , 16 , 17 ], such as single leg hopping distance [ 16 ] or standing jump distance [ 17 ] were also improved significantly after plyometric training in athletes. Plyometric exercise of the lower extremities generally involves repetitive jump-landing movements and agility tasks with rapid changes of directions [ 10 , 18 ]. Such movements involve instantaneous stretch-shortening cycles that actuate the mechanical or proprioception receptors on the ligaments of the foot or tendons around the ankle joint due to the muscle spindle is more sensitive to the instantaneous stretching [ 19 ], and are thus of great potential benefit in improving the reposition sense of the ankle joint and enhancing the balance ability accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of plyometric exercise on balance control were not investigated. Plyometric exercise of the lower extremities generally involves repetitive jump-landing movements and agility tasks with rapid changes of direction [12]. Such movements actuate the mechanical or proprioception receptors on the ligaments of the foot or tendons around the ankle joint, and are thus of great potential bene t in improving the position sense of the ankle joint and enhancing the balance ability accordingly.…”
Section: Introductionmentioning
confidence: 99%